THE EFFECT OF LOCATION, PRODUCT DESIGN AND QUALITY OF SERVICE TO CUSTOMER LOYALTY IN THE AIRA BAKERY STORE, AIR BATU, ASAHAN REGENCY - Fhitri, Nisfu (International Journal of Public Budgeting, Accounting and Finance, 2021)
This study aims to determine the effect of simultaneous and partial location, product design and service quality on customer loyalty. This research used quantitative method. The number of samples taken was 87 people. Equation of multiple linear regression analysis, obtained value of Y = 0.689 + 0.319X1 + 0.409X2 + 0.501X3 + e. That is, the independent variable consisting of location, product design and service quality has a positive effect on customer loyalty. F-test results explain, the value of F is 12.320 which is > F-table 2.71 and the significance value is 0.000 < 0.05, meaning that simultaneously location (X1), product design (X2) and service quality (X3) affect customer loyalty (Y). The t-test results explain, location (X1), produces a t-value of 2.165> t-table of 1.988 and a significance value of 0.033 <0.05. Product design (X2), yielding t-value 2.670> t-table 1.988 and significance value 0.009 <0.05 and service quality (X3), yielding t-value 2.874> t-table 1.988 and significance value 0.005 <0.05 then H2 is accepted. That is, location, product design and service quality (X3) have a partial effect on customer loyalty. The results of the coefficient of determination test produce Adjusted R-Square value obtained by 0.283. This means that the independent variable consisting of location (X1), product design and service quality is able to explain the dependent variable that is customer loyalty by 28.3%, while the remaining 71.7% is explained by other variables not examined in this study.